Improvement Of Mathematics Learning Outcomes About Flat Building Area Through Stad-Type Cooperative Learning Methods For Grade III Students Of SD Negeri 005 Kepenuhan - Juniar Juniar (Indonesian Journal of Basic Education, 2023)
The formulation of the problem in this study is Whether the STAD-type cooperative learning method can improve mathematics learning outcomes about flat building area in grade 3 semester 2 students of SDN 005 Kepenuhan 2021/2022?" The purpose of this study is to improve the learning outcomes of mathematics Class III Semester 2 on the subject matter of calculating the flat building area at SDN 005 Kepenuhan in 2021/2022. The results showed that the use of the STAD cooperative method can improve student learning outcomes in grade III mathematics subjects at SDN 005 Kepenuhan. This can be seen from the First Cycle of using the STAD type of Cooperative method, there was an increase, namely from 17 students as many as 11 students (64.70%) who achieved the Minimum Completion Criteria (KKM). And there was a significant increase in cycle II, namely as many as 13 students (76.47%) who achieved the Minimum Completion Criteria (KKM)